Array - Amalia, Mia; Wahyuningsih, Fahmi (LATERNE, 2022)
Abstract Listeningisoneofthelanguageskillsthathavetheadvantageofseveralotherskills,because listeningprovidesperceptionsorassumptionsthatproducenewthinking(Grotjahn,2010).Ittakes innovationtosupportlisteningskills.Oneoftheinnovationsistheuseofpodcastmedia,whichisa technologicaldevelopmentinthisdigitalera.From theresultsofresearchconductedby(Madiope, 2013:4)thataudiomediapodcastform isinhighdemand.Theproblem thatarisesishow the contentoftheMeineFamiliepodcastasateachingmaterialforgermanlisteningskillsclassXI semester1.Relatedtothis,ananalysiswasconductedthatobtainedthesuitabilityofthecontentof podcastmaterialentitledMeineFamiliebasedonthe2013curriculum asteachingmaterialand utilizingtechnologyinlearning.Thisarticleisanalyzedwiththetheoryofdatacontentanalysis techniques(Sugiyono,2008:244)withthestagesofdecryptingpodcastcontent,reducingthe informationobtained,andselectingthecoreoftheteachingmaterialcontained.From theresultsof theanalysisusinglikertscalecalculations(Sugiyono,2009:14)itwasfoundthatthepercentageof materialcontentintheMeineFamiliepodcastasateachingmaterialforlisteningskillsinclassXI semester1showedthat98%wasverysuitablebasedonthe2013curriculum. Keywords:ListeningSkills,Podcasts,Curriculum2013